Changes in Social Network Size Are Associated With Cognitive Changes in the Oldest-Old - Röhr, Susanne; Löbner, Margrit; Gühne, Uta; Heser, Kathrin; Kleineidam, Luca; Pentzek, Michael; Fuchs, Angela; Eisele, Marion; Kaduszkiewicz, Hanna; König, Hans-Helmut; Brettschneider, Christian; Wiese, Birgitt; et al. (Frontiers in Psychiatry, 2020)
Objectives Social isolation is increasing in aging societies and several studies have shown a relation with worse cognition in old age. However, less is known about the association in the oldest-old (85+); the group that is at highest risk for both social isolation and dementia. Methods Analyses were based on follow-up 5 to 9 of the longitudinal German study on aging, cognition, and dementia in primary care patients (AgeCoDe) and the study on needs, health service use, costs, and health-related quality of life in a large sample of oldest-old primary care patients (AgeQualiDe), a multi-center population-based prospective cohort study. Measurements included the Lubben Social Network Scale (LSNS-6), with a score below 12 indicating social isolation, as well as the Mini-Mental Status Examination (MMSE) as an indicator of cognitive function. Results Dementia-free study participants (n = 942) were M = 86.4 (SD = 3.0) years old at observation onset, 68.2% were women. One third (32.3%) of them were socially isolated. Adjusted linear hybrid mixed effects models revealed significantly lower cognitive function in individuals with smaller social networks (β = 0.5, 95% CI = 0.3–0.7, p < .001). Moreover, changes in an individual’s social network size were significantly associated with cognitive changes over time (β = 0.2, 95% CI = 0.1–0.4, p = .003), indicating worse cognitive function with shrinking social networks. Conclusion Social isolation is highly prevalent among oldest-old individuals, being a risk factor for decreases in cognitive function. Consequently, it is important to maintain a socially active lifestyle into very old age. Likewise, this calls for effective ways to prevent social isolation.